Gambling Disorder in Türkiye: A Systematic Review and Meta-Analysis Study - Yeti̇m, Birol; Kovancı, Merve; Karaca, Meryem Mine; Topcu, Dilara Sevi̇nç; Gökler, Mehmet Enes; Maral, Işıl (Springer Science and Business Media Deutschland GmbH, 2026)
Purpose of Review: Gambling disorder is recognized as a behavioral addiction characterized by persistent and recurrent problematic gambling behavior that leads to clinically significant impairment or distress. Despite growing international research, comprehensive evidence on gambling disorder in Türkiye remains limited. This study aims to systematically review existing research on gambling disorder in Türkiye and provide a pooled prevalence estimate based on available studies. Recent Findings: A systematic search was conducted in March 2025 across Web of Science, PubMed, and Scopus databases using MeSH-based keywords. A total of 182 records were identified, and 35 studies met the inclusion criteria for systematic review. Among these, 14 studies reported prevalence data and were included in the meta-analysis. Due to high heterogeneity (I² = 97.7%), a random-effects model was applied. The pooled prevalence of gambling disorder across included studies was estimated at 4.0% (95% CI: 2.0%–8.0%). However, this estimate is derived from heterogeneous, predominantly non-representative samples (e.g., students and clinical populations) and should not be interpreted as a nationally representative prevalence estimate. While several studies proposed prevention and intervention strategies, none of these approaches have been formally evaluated within the Turkish context. Summary: The findings suggest that gambling disorder represents an emerging public health concern in Türkiye. Targeted prevention strategies focusing on high-risk groups, particularly young individuals and males, are needed. Public awareness campaigns, screening strategies, and improved access to counseling and treatment services may contribute to reducing gambling-related harm. © The Author(s) 2026.
Keywords: Addiction; Gambling Disorder; Meta-Analysis; Systematic Review; Türkiye